Değişen Yükseköğretim Sistemini Sosyokültürel ve Mekânsal Bağlamlarda Yeniden Düşünmek - Ayten, Asim Mustafa; Gover, Ibrahim Hakan (DEOMED PUBL, ISTANBUL, GUR SOK 7-B, FIKIRTEPE 34720 KADIKOY, ISTANBUL, 00000, TURKEY, 2020)
Education and research are vital for social development and progress. The changing sociocultural structures and new needs have resulted in some important functional changes in higher education systems with a deep impact on universities serving these needs at the highest level. Besides experiencing these functional changes, the universities today have become spaces of socialization with their social, cultural and sports facilities, replacing their traditional spatial role of offering education only. The local dynamics changing with globalization have now reshaped the global and local roles of universities, highlighting the added value they provide to the society. Sociocultural changes trigger all these functional and structural changes in universities. Therefore, sociocultural factors and their importance should not be ignored in a changing higher education system. In this study, the impact of sociocultural factors with their related spatial structures on world higher education system will be analyzed within their historical contexts, and some suggestions for future universities will be offered considering the current changes. In the first part of the study, the changes in societies and universities will be presented within the historical context. In the second part, the spatial forms and structures of universities will be discussed. In the third part, the catalytic effects of the specific sociocultural factors will be highlighted and elaborated on. Finally, some suggestions will be made for the universities of the future in the light of the current situation and the data available.
Reconsidering the Changing Higher Education System from Sociocultural and Spatial Perspectives
Keywords: Campus planning and design; globalization; higher education; sociocultural structure